PELUANG DAN TANTANGAN DAKWAH USTADZ HANAN ATTAKI - Permatasari, Bunga; Milladiya, Izza (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2023)
The purpose of this research is to find out and identify opportunities and challenge Ustadz Hanan Attaki's preaching through Youtube media. The results of the research found by researchers, namely that there are several opportunities and challenges for preaching carried out by Ustadz Hanan Attaki, especially through Youtube media, the opportunities include : 1.) Become popular and liked by teenagers, 2.) Become multimedia content, 3.) Become a source of inspiration and knowledge for many people. Besides that, the challenges that Ustadz Hanan Attaki must face are: 1.) There are many different opinions and understandings in society. 2.) Slander and attacks on Ustadz Hanan Attaki with false accusations or defamation of his name. This research also explains about da'wah media, as it is currently still widespread da'wah using mass media. The mass media has many strengths that make it very important and very strategic especially when used in preaching. Especially as imagery and formation of Islamic behavior in society